Konsep Islam Wasathiyah dalam Al-Qur’an; Analisis Munasabah Q.S Al-Baqarah ayat 143 - Heri Aulia Rahman; Aspandi Aspandi (Saintifika Islamica, 2023)
The systematic beauty of the Qur'an is proof of its miracles. Because of the beauty of its systematics, it is the basis for the existence of reasonable knowledge (relatedness) of the Qur'an.  To express the interrelation of verses in the Qur'an about the concept of wasathiyah Islam in the view of M. Quraish Shihab, it is necessary to sharpen the views of the mufassir in presenting the text of the Qur'an related to the concept of Wasathiyah Islam in the perspective of M. Quraish Shihab. The purpose of this study is to explain the Islamic concept of wasathiyah by analyzing plausibility in the Qur'an Surat al-Baqarah verse 143. This research is included in the type of qualitative research using a library research approach. This study found that there is a connection between the text in Q.S. Al-Baqarah: 143, namely between the discussion of "Ummatan Wasatha" and the discussion of "Qibla direction". Where "wasatha" which means middle is likened to the position of the Kaaba in the middle of the earth. This means that the middle position makes people impartial to the left and right, something that can lead people to do justice